A polythiophene-based photothermal fabric based on dextran sulfate as a template and its preparation method and application
By grafting dextran sulfate on the fiber surface and performing in-situ polymerization, the problem of PEDOT uniformity on the fiber is solved, stable and efficient photothermal effect and durability are achieved, and the fabric has good photothermal sterilization function.
Patent Information
- Application Number
- CN202310092335.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-10
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-02-10
AI Technical Summary
In the prior art, it is difficult to achieve uniform polymerization of PEDOT on the fiber, resulting in different PEDOT content and molecular weights deposited on the surface of the fiber product, affecting the uniformity, stability and durability of the photothermal function of the fabric.
By grafting dextran sulfate on the surface of the fiber, a thiophene polymerization template with covalent bonding with the fibers is formed, and in situ polymerization of 3,4-ethylene dioxythiophene monomers is carried out to build a stable, efficient and long-lasting photothermal fabric.
It realizes uniform distribution and efficient deposition of PEDOT on the fiber surface, improves the uniformity and durability of the photothermal effect, and gives the fabric an efficient photothermal sterilization function.
Smart Images

Figure BDA0004070676120000071
Abstract
Description
Technical Field
[0001] The invention relates to a polythiophene-based photothermal fabric based on dextran sulfate as a template and a preparation method and application thereof, belonging to the technical field of functional textile processing. Background Art
[0002] In recent years, the development of new textiles with special functions has received increasing attention, especially textiles with self-heating functions under certain conditions are popular in autumn and winter clothing fabrics, outdoor materials and home textile products. At present, self-heating textiles are divided into two different types, including conductive heating driven by low-voltage power supply and photothermal heating irradiated by visible light or near-infrared light. Conductive heating textiles are conductive media such as graphene, carbon nanotubes, MXene nanosheets or conjugated polymers (such as polyaniline, polythiophene, polypyrrole) applied to the surface of fiber products by impregnation or coating finishing, and the fiber surface generates Joule heat under the current drive of an external power supply to achieve the surface temperature of the textile. Photothermal heating is to select a photothermal medium that has an absorption effect on visible light or near-infrared, and the photothermal effect of the medium under light conditions causes the surface temperature of the textile to rise rapidly. Common photothermal media include conjugated polymers, nano copper sulfide particles, carbon quantum dots, graphene and other carbon nanosheets / nanotubes, etc. Compared with electric heating fabrics, photothermal fabrics do not require external power supply during use. They only require irradiation with a light source of a certain intensity to achieve a rapid increase in fiber surface temperature. They have the advantage that photothermal effects are easier to implement.
[0003] Poly (3,4-ethylenedioxythiophene) (PEDOT) is a common conjugated polymer with excellent conductivity and photothermal effect, which can be used in photothermal textile processing. PEDOT macromolecules are insoluble in water. In the preparation process, sodium polystyrene sulfonate (PSS) with excellent hydrophilicity is usually used as a template to obtain a water-soluble PEDOT:PSS system through free radical polymerization, which is used in the preparation of conductive textiles, electrothermal or photothermal fabrics. On the other hand, there are still some shortcomings in the preparation of polythiophene-based photothermal fabrics using the PEDOT:PSS system, including: (1) when the impregnation method is used, due to the high water solubility of the PEDOT:PSS system, there is a problem of weak bonding between PEDOT and the fiber (i.e., poor washability), resulting in a decrease in the photothermal efficiency and poor photothermal stability of the polythiophene-based photothermal fabric; (2) when the adhesive and the PEDOT:PSS system are used in combination and the fabric is processed by the coating method, although the stability of the photothermal effect obtained by the fabric is improved, the feel, air permeability and drape of the fabric will be significantly reduced, reducing the wearing comfort of the photothermal fabric.
[0004] In order to solve the above problems, the existing technology has adopted the method of first introducing vinyl on the fiber surface, and then grafting and polymerizing with benzenesulfonic acid / sodium benzenesulfonate monomers to achieve PEDOT polymerization guided by grafting PSS template on the fiber surface. The defect of this method is that during grafting polymerization, the molecular weight of PSS formed by free radical polymerization on the fiber surface is difficult to control (that is, the length of the PSS molecular chain formed by polymerization is polydisperse), and it is difficult to achieve uniform polymerization of PEDOT on the fiber, resulting in different contents and molecular weights of PEDOT deposited on the surface of the fiber product, which affects the uniform stability of the conductive and photothermal functions of the fabric.
[0005] Therefore, how to construct a polythiophene-based photothermal fabric that has good uniformity, stable and efficient, and lasting photothermal effect, while also having excellent wearing comfort is a technical problem that needs to be solved urgently. Summary of the invention
[0006] [Technical issues]
[0007] It is difficult to achieve uniform polymerization of PEDOT on fibers in the existing technology, resulting in different contents and molecular weights of PEDOT deposited on the surface of fiber products, affecting the uniformity, stability and durability of the photothermal function of the fabric.
[0008] [Technical solution]
[0009] In view of the above technical problems, the present invention provides a polythiophene-based photothermal fabric based on dextran sulfate as a template, and a preparation method and application thereof; that is, the present invention forms a thiophene polymerization template covalently bonded to the fiber by grafting dextran sulfate on the fiber surface; and then in situ polymerization of 3,4-ethylenedioxythiophene monomer on the fiber surface is performed to construct a photothermal fabric with stable, efficient and lasting photothermal effect.
[0010] The object of the present invention is to provide a method for preparing a polythiophene-based photothermal fabric based on dextran sulfate as a template, the method comprising the following steps:
[0011] (1) Grafting dextran sulfate on the fiber surface: The fabric is immersed in a dextran sulfate solution and a cross-linking agent is added to promote the grafting reaction of dextran sulfate on the fiber surface;
[0012] (2) In-situ polymerization of polythiophene on the fiber surface: The fabric treated in step (1) is immersed in an ethanol solution of 3,4-ethylenedioxythiophene monomer, and an initiator is added to catalyze the in-situ polymerization of 3,4-ethylenedioxythiophene on the fiber surface to prepare a polythiophene-based photothermal fabric; the polythiophene-based photothermal fabric is then washed and dried.
[0013] In one embodiment, the fabric in step (1) comprises a knitted fabric or a woven fabric formed from one or more of cotton, linen, silk, wool, viscose or tencel.
[0014] In one embodiment, the cross-linking agent in step (1) includes one or more of ethylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether or four-arm PEG-ethylene oxide.
[0015] In one embodiment, the molecular weight of the dextran sulfate in step (1) is 40 to 60 kDa.
[0016] In one embodiment, the concentration of the dextran sulfate solution in step (1) is 5-20 g / L, the concentration of the cross-linking agent is 1-5 g / L, the bath ratio is 1:8-20, the temperature of the reaction system is 50-60°C, the pH range is 8-9, and the time is 1-2 h.
[0017] In one embodiment, the initiator in step (2) is ammonium persulfate or horseradish peroxidase.
[0018] In one embodiment, the volume ratio of ethanol to water in the ethanol solution of step (2) is 1:6, and the concentration of 3,4-ethylenedioxythiophene is 5-10 g / L.
[0019] In one embodiment, the concentration of the initiator in step (2) is 1-2 g / L.
[0020] In one embodiment, the mass ratio of the 3,4-ethylenedioxythiophene to the initiator is 5-10:1-2.
[0021] In one embodiment, the polymerization reaction conditions are: bath ratio 1:8-20, temperature 30-40°C, pH range 6-7, time 2-6h.
[0022] In one embodiment, the washing in step (2) is performed with a 25% ethanol solution at 25-30°C.
[0023] In one embodiment, the drying temperature in step (2) is 50-60°C.
[0024] Another object of the present invention is to provide a polythiophene-based photothermal fabric prepared by the above method.
[0025] The third object of the present invention is to provide an application of the polythiophene-based photothermal fabric described above in the preparation of functional textiles.
[0026] [Beneficial Effects]
[0027] The present invention first grafts dextran sulfate on the fiber surface to form a template for inducing the polymerization of thiophene monomers; then, 3,4-ethylenedioxythiophene monomers are catalyzed by an initiator to polymerize in situ on the fiber surface to prepare polythiophene-based photothermal fabrics; finally, the fabric is thoroughly cleaned and dried to obtain a photothermal fabric with a long-lasting and stable photothermal effect. Compared with the photothermal fabric preparation method of using a PSS template grafted on the fiber surface and then performing a PEDOT polymerization deposition method, a PEDOT:PSS direct impregnation method or a coating method to apply it to the fabric surface, etc., the method described in the present invention has the following advantages:
[0028] (1) Uniform photothermal effect: The molecular weight of the dextran sulfate grafted on the fiber surface is stable, which is conducive to the polymerization of thiophene monomers on the fiber surface through the template effect, forming PEDOT with uniform molecular chain length, promoting the uniform distribution of photothermal medium on the fiber surface, and improving the uniformity of the photothermal effect of the fabric;
[0029] (2) High photothermal efficiency: With the help of ethylene glycol diglycidyl ether, dentran sulfate (DS) is grafted onto hydroxyl-containing fibers through an epoxy end-group ring-opening addition reaction, forming a 3,4-ethylenedioxythiophene polymerization template on the fiber surface, which is beneficial to the in-situ deposition of poly 3,4-ethylenedioxythiophene monomer on the fiber surface, increasing the amount of photothermal polymer deposited on the fiber and improving the photothermal conversion efficiency of the fabric surface.
[0030] (3) Long-lasting photothermal effect: The present invention first grafts the DS molecules onto the fiber surface by covalent bonds, which is beneficial to the in-situ polymerization of PEDOT on the fiber surface, forming a PEDOT:DS system with strong binding force, improving the washability of the photothermal medium on the fabric, and enabling the fabric to obtain a long-lasting and stable photothermal effect.
[0031] (4) Strong photothermal sterilization property: PEDOT deposited in situ on the fiber surface using DS as a template not only gives the fabric a photothermal effect, but also heats up and kills bacteria such as Escherichia coli and Staphylococcus aureus in a short time under light conditions, giving the fabric a high-efficiency photothermal sterilization function. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described in detail below through specific embodiments. However, it is necessary to point out that the following embodiments are only used to describe the content of the invention and do not constitute a limitation on the protection scope of the present invention.
[0033] Silk power spinning is a type of silk woven fabric, purchased from Jiangsu Xinyuan Cocoon Silk Co., Ltd.;
[0034] All-wool gabardine is a type of wool woven fabric, purchased from Wuxi Xiexin Wool Textile Co., Ltd.
[0035] Pure cotton jersey is a type of cotton knitted fabric, purchased from Jiangyin Zhenhong Printing and Dyeing Co., Ltd.
[0036] Horseradish peroxidase was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and the enzyme activity was 300 U / mg;
[0037] Dextran sulfate was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with molecular weights of 40 kDa and 60 kDa, respectively.
[0038] Example 1
[0039] A method for preparing a polythiophene-based photothermal fabric based on dextran sulfate as a template comprises the following steps:
[0040] (1) Grafting dextran sulfate on the fiber surface: The silk electrospun was immersed in a dextran sulfate solution with a molecular weight of 40 kDa, and a cross-linking agent ethylene glycol diglycidyl ether was added to react, thereby promoting the grafting of dextran sulfate on the fiber surface with the help of the cross-linking agent;
[0041] Treatment process prescription and conditions: dextran sulfate 5g / L, ethylene glycol diglycidyl ether 1g / L, bath ratio 1:8, solution temperature 50℃, pH 8, reaction time 1h;
[0042] (2) In-situ polymerization of polythiophene on the fiber surface: The silk treated in step (1) is immersed in an ethanol solution of 3,4-ethylenedioxythiophene monomer by electrospinning, and ammonium persulfate is added to catalyze the in-situ polymerization of 3,4-ethylenedioxythiophene on the silk surface to prepare a polythiophene-based photothermal fabric;
[0043] Treatment process prescription and conditions: 3,4-ethylenedioxythiophene 5g / L, ammonium persulfate 1-2g / L, ethanol to water volume ratio of 1:6; bath ratio 1:8, temperature 30℃, pH 6, treatment time 2h;
[0044] (3) Fabric washing and drying post-treatment: The fabric treated in step (2) is washed with 25% ethanol solution at 25°C, and finally dried at 60°C.
[0045] Example 2
[0046] A method for preparing a polythiophene-based photothermal fabric based on dextran sulfate as a template comprises the following steps:
[0047] (1) Grafting dextran sulfate onto the fiber surface: The whole wool gabardine is immersed in a dextran sulfate solution with a molecular weight of 40 kDa, and a cross-linking agent ethylene glycol diglycidyl ether is added to react, thereby promoting the grafting of dextran sulfate onto the fiber surface with the help of the cross-linking agent;
[0048] Treatment process prescription and conditions: dextran sulfate 20g / L, ethylene glycol diglycidyl ether 5g / L, bath ratio 1:20, solution temperature 60℃, pH 9, reaction time 2h;
[0049] (2) In-situ polymerization of polythiophene on the fiber surface: the all-wool gabardine treated in step (1) is immersed in an ethanol solution of 3,4-ethylenedioxythiophene monomer, and ammonium persulfate is added to catalyze the in-situ polymerization of 3,4-ethylenedioxythiophene on the wool surface to prepare a polythiophene-based photothermal fabric;
[0050] Treatment process prescription and conditions: 3,4-ethylenedioxythiophene 10g / L, ammonium persulfate 2g / L, ethanol to water volume ratio of 1:6; bath ratio 1:20, temperature 40℃, pH 7, treatment time 6h;
[0051] (3) Fabric washing and drying post-treatment: The fabric treated in step (2) is washed with 25% ethanol solution at 25°C, and finally dried at 60°C.
[0052] Example 3
[0053] A method for preparing a polythiophene-based photothermal fabric based on dextran sulfate as a template comprises the following steps:
[0054] (1) Grafting dextran sulfate on the fiber surface: The pure cotton jersey is immersed in a dextran sulfate solution with a molecular weight of 60 kDa, and a cross-linking agent, neopentyl glycol diglycidyl ether, is added to react, so that the dextran sulfate is grafted on the fiber surface with the help of the cross-linking agent;
[0055] Treatment process prescription and conditions: dextran sulfate 20g / L, neopentyl glycol diglycidyl ether 5g / L, bath ratio 1:20, solution temperature 60℃, pH 9, reaction time 2h;
[0056] (2) In-situ polymerization of polythiophene on the fiber surface: the pure cotton jersey treated in step (1) is immersed in an ethanol solution of 3,4-ethylenedioxythiophene monomer, and horseradish peroxidase is added to catalyze the in-situ polymerization of 3,4-ethylenedioxythiophene on the wool surface to prepare a polythiophene-based photothermal fabric;
[0057] Treatment process prescription and conditions: 3,4-ethylenedioxythiophene 7.5g / L, horseradish peroxidase 2g / L, ethanol to water volume ratio of 1:6; bath ratio 1:20, temperature 40℃, pH 7, treatment time 6h;
[0058] (3) Fabric washing and drying post-treatment: The fabric treated in step (2) is washed with 25% ethanol solution at 25°C, and finally dried at 60°C.
[0059] Comparative Example 1
[0060] The silk electrospun in Example 1 was not subjected to any treatment.
[0061] Comparative Example 2
[0062] The silk electrospun in Example 1 is only processed through steps (2) and (3) without being processed through step (1).
[0063] Comparative Example 3
[0064] The silk electrospun in Example 1 was processed through steps (1) to (3), but no cross-linking agent ethylene glycol diglycidyl ether was added in step (1).
[0065] Comparative Example 4
[0066] The silk electrospinning in Example 1 was treated by immersion in a conventional PEDOT:PSS solution system, wherein a 20 g / L PEDOT:PSS aqueous solution was treated for 2 h at a bath ratio of 1:8, 30°C, and pH 6, then washed with a 25% ethanol solution at 25°C, and finally dried at 60°C.
[0067] Comparative Example 5
[0068] The electric-spun silk in Example 1 was immersed in a 2 g / L methacrylic anhydride solution and treated at 0°C and pH 7 for 4 hours; after washing, the fabric was immersed in a 5 g / L styrene sulfonic acid solution, 15 g / L ferrous chloride and 5 g / L hydrogen peroxide were added, and the treatment was carried out at 50°C and pH 4 for 3 hours to graft polystyrene sulfonic acid on the fiber; 5 g / L thiophene ethanol solution was further added to the system, and the treatment was carried out at 0°C and pH 1.5 for 3 hours to promote the formation of polythiophene on the fabric surface, and finally the fabric was washed and dried.
[0069] Comparative Example 6
[0070] The all-wool gabardine in Example 2 was not subjected to any treatment.
[0071] Comparative Example 7
[0072] The all-wool gabardine in Example 2 is only processed through steps (2) and (3) without being processed through step (1).
[0073] Comparative Example 8
[0074] The wool gabardine in Example 2 is treated through steps (1) to (3), but in step (1) no cross-linking agent ethylene glycol diglycidyl ether is added.
[0075] Comparative Example 9
[0076] The wool gabardine in Example 2 was treated by immersion in a conventional PEDOT:PSS solution system, wherein the PEDOT:PSS solution was 20 g / L, and the fabric was treated for 6 hours at a bath ratio of 1:20, 40°C, and pH 7; then the fabric was washed with a 25% ethanol solution at 25°C, and finally dried at 60°C.
[0077] Comparative Example 10
[0078] The wool gabardine was immersed in 4g / L methacrylic anhydride solution and treated at 4℃ and pH 8 for 6 hours. After washing, the fabric was immersed in 20g / L styrene sulfonic acid solution, and 20g / L ferrous chloride and 8g / L hydrogen peroxide were added. The treatment was carried out at 60℃ and pH 5 for 3 hours to graft polystyrene sulfonic acid on the fiber. 10g / L thiophene ethanol solution was further added to the system and treated at 0℃ and pH 2.5 for 4 hours to promote the formation of polythiophene on the fabric surface. Finally, the fabric was washed and dried.
[0079] Comparative Example 11
[0080] The pure cotton jersey in Example 3 was not subjected to any treatment.
[0081] Comparative Example 12
[0082] The pure cotton jersey fabric in Example 3 is only treated by steps (2) and (3) but not by step (1).
[0083] Comparative Example 13
[0084] The pure cotton jersey fabric in Example 3 is treated by steps (1) to (3), but no cross-linking agent ethylene glycol diglycidyl ether is added in the treatment of step (1).
[0085] Comparative Example 14
[0086] The pure cotton jersey in Example 3 was treated with a traditional PEDOT:PSS system solution, wherein the PEDOT:PSS solution was 20 g / L, and the fabric was treated for 6 hours at a bath ratio of 1:20, 40°C, and pH 7; then the fabric was washed with a 25% ethanol solution at 25°C, and finally dried at 60°C.
[0087] Comparative Example 15
[0088] The pure cotton jersey was immersed in 4g / L methacrylic anhydride solution and treated at 4℃ and pH 8 for 6 hours. After washing, the fabric was immersed in 20g / L styrene sulfonic acid solution, and 20g / L ferrous chloride and 8g / L hydrogen peroxide were added. It was treated at 60℃ and pH 5 for 3 hours to graft polystyrene sulfonic acid on the fiber. 7.5g / L thiophene ethanol solution was further added to the system and treated at 0℃ and pH 2.5 for 4 hours to promote the formation of polythiophene on the fabric surface. Finally, the fabric was washed and dried.
[0089] The fabrics obtained in Examples 1 to 3 and Comparative Examples 1 to 15 were respectively subjected to the following tests:
[0090] (1) Photothermal effect evaluation: A xenon lamp was used to simulate sunlight (referred to as simulated light source) at 200 mW / cm 2 Irradiate the sample for 5 minutes, then use an infrared temperature gun to measure the temperature of four different positions on the sample surface at a vertical distance of 30 cm (the distance between adjacent positions is 10 cm), and calculate the average temperature T1 and standard deviation SD1, which are recorded as T1±SD1;
[0091] (2) Evaluation of bactericidal effect: Escherichia coli was inoculated on the surface of the samples, and after irradiation with the above-mentioned simulated light source for 5 minutes, the colonies on the surface of the samples were washed with buffer and collected. The samples that were not irradiated with the simulated light source and without any treatment were used as references, and the colonies were cultured using the method described in GB / T 20944.3-2008, and the bactericidal rate of the samples after irradiation was calculated;
[0092] (3) Determine the fabric drape coefficient D by referring to the image processing method in GB / T 23329-2009;
[0093] (4) The above sample was washed with 1.0 g / L detergent at 40°C for 1 hour, and then irradiated with the simulated light source of the same intensity for 5 minutes after drying at room temperature. Then, the temperature of four different positions on the sample surface was measured at a vertical distance of 30 cm using an infrared temperature measuring gun (the distance between adjacent positions was 10 cm). The average temperature T2 and the standard deviation SD2 were calculated and recorded as T2±SD2 to evaluate the long-term stability of the photothermal effect of the fabric. The above test results are shown in Table 1.
[0094] Table 1
[0095]
[0096]
[0097] From Table 1, we can see that:
[0098] a. After the photothermal fabrics (Example 1, Example 2, and Example 3) prepared by the method of the present invention were irradiated with a simulated light source, the surface temperature T1 of the fabrics was relatively high, and the standard deviation value SD1 was relatively small, indicating that the polyglucose sulfate (DS) template grafting effectively promoted the grafting polymerization of PEDOT on the fiber surface, producing a stable and efficient photothermal effect; at the same time, the surface temperature of the fabrics was relatively high after irradiation, and had a high sterilization rate against Escherichia coli (all greater than 99%); the drape coefficient D of the finished fabrics did not change significantly compared with the untreated sample, indicating that the fabrics not only had a good photothermal effect, but also had a good feel; after the fabrics finished by the method of the present invention were washed with standard water, the surface temperature T2 was tested again under the same irradiation conditions, and the result was similar to the temperature T1, and the standard deviation value was also relatively low, verifying that the photothermal medium PEDOT:DS on the surface of the sample had a high bonding strength, so that the fabrics had a long-lasting and stable photothermal effect.
[0099] b. After the samples without any treatment (Comparative Example 1, Comparative Example 6, Comparative Example 11) were irradiated with a simulated light source, the temperature T1 detected on the fabric surface was low, and there was no obvious photothermal effect; the samples had no photothermal sterilization effect on Escherichia coli; after the fabric was washed with standard water, the surface temperature T2 under the same irradiation conditions was also low when tested again.
[0100] c. After the samples (Comparative Example 3, Comparative Example 7, Comparative Example 12) were irradiated with a simulated light source, the surface temperature T1 of the fabric was higher than that of the untreated sample, indicating a certain photothermal effect; the photothermal sterilization effect of the samples was evaluated with reference to the method mentioned above, and the sterilization rates of the samples against Escherichia coli were all <40%, indicating that the samples were not pre-grafted with a DS template, resulting in a small amount of PEDOT deposited on the fiber surface, and the photothermal effect and sterilization rate of the fabric were also low; after the samples were washed with standard water, the surface temperature T2 of the fabric was tested again under the same irradiation conditions, and the surface temperature was further reduced, verifying that not only was the amount of PEDOT deposited on the fiber surface small, but the bonding strength was also low, and the stability of the photothermal effect of the fabric was poor.
[0101] d. After the samples (Comparative Example 3, Comparative Example 8, Comparative Example 13) were treated only by steps (1) to (3) but without adding the cross-linking agent ethylene glycol diglycidyl ether in the treatment of step (1) were irradiated with a simulated light source, the surface temperature T1 of the fabric was similar to that of the samples treated only by steps (2) and (3); the simulated light source irradiation was performed according to the method described above, and the bactericidal rates of the samples against Escherichia coli were measured to be <50%, indicating that if the cross-linking agent ethylene glycol diglycidyl ether is not added in the DS immersion treatment, the fiber surface lacks a template for orderly inducing the polymerization deposition of polythiophene, and the amount of PEDOT deposited in situ on the fiber surface during the catalytic polymerization is also small, so the photothermal effect and bactericidal rate of the fabric are low; after standard water washing, the surface temperature T2 of the samples under the same irradiation conditions was tested again, and the results were similar to those of the samples treated only by steps (2) and (3), that is, the amount of PEDOT deposited on the fiber surface is small, the bonding fastness is also low, and the photothermal effect stability of the fabric is poor.
[0102] e. The samples were immersed in the traditional PEDOT:PSS solution system. After the samples were treated under the same temperature and pH conditions (Comparative Example 4, Comparative Example 9, Comparative Example 14) and irradiated with a simulated light source, the surface temperature T1 of the fabric was similar to that of the samples treated by the method described in the present invention (Example 1, Example 2, Example 3). The photothermal sterilization effect was evaluated by referring to the method described. The sterilization rates of the samples against Escherichia coli were all >98%, indicating that the PEDOT:PSS solution system had a certain photothermal sterilization effect. After standard water washing, the surface temperature T2 of the samples under the same irradiation conditions was tested again. As a result, the measured surface temperature of the samples decreased to a large extent, and the temperature deviation value SD2 was large, indicating that the PEDOT:PSS photothermal medium on the fiber surface was partially lost during water washing. The reason for this is that the water solubility of PEDOT:PSS is high and the PSS template does not form a covalent bond with the fiber, resulting in poor stability of the photothermal effect of the fabric.
[0103] f. After irradiation with a simulated light source, the fabric surface temperature T1 of the samples obtained by first grafting a PSS template on the fiber surface and then in-situ depositing PEDOT (Comparative Example 5, Comparative Example 10, Comparative Example 15) was slightly lower than that of the finished samples (Example 1, Example 2, Example 3) described in the present invention, but the temperature standard deviation values (SD1) at different positions on the sample surface were large, indicating that although the photothermal effect on the fabric surface was good, the uniformity was insufficient; at the same time, the surface temperature of the fabric was high after irradiation, and the sterilization rate for Escherichia coli was also high; the drape coefficient D of the finished fabric did not change significantly compared with the untreated sample; the photothermal effect of the fabric decreased less after washing, but there was also a disadvantage of poor uniformity of the photothermal effect on the fabric surface, which was manifested in a large standard deviation value SD2, which was higher than the standard deviation value of the sample finished by the method described in the present invention.
[0104] It can be seen that the samples of Example 1, Example 2 and Example 3 treated by the method of the present invention not only have a higher photothermal effect (the surface temperature of the fabric is high and the standard deviation value is low after irradiation), but also have good wash resistance after finishing (after standard washing, the maximum temperature of the fabric surface under the same irradiation conditions does not change significantly). The irradiated fabric also has a strong photothermal sterilization effect; compared with the untreated sample, the drape of the fabric has not changed significantly, maintaining the good feel of the original fabric.
[0105] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing a polythiophene-based photothermal fabric based on dextran sulfate as a template, characterized in that: The method comprises the following steps: (1) Grafting dextran sulfate onto the fiber surface: the fabric is immersed in a dextran sulfate solution, and a cross-linking agent is added to promote the grafting of dextran sulfate onto the fiber surface by means of the cross-linking agent; the cross-linking agent includes one or more of ethylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether or four-arm PEG-ethylene oxide; (2) In-situ polymerization of polythiophene on the fiber surface: the fabric treated in step (1) is immersed in an ethanol solution of 3,4-ethylenedioxythiophene monomer, an initiator is added to catalyze the in-situ polymerization of 3,4-ethylenedioxythiophene on the fiber surface, and a polythiophene-based photothermal fabric is prepared; the polythiophene-based photothermal fabric is then washed and dried; the molecular weight of the dextran sulfate in step (1) is 40 to 60 kDa; the conditions of the polymerization reaction are: bath ratio 1:8 to 20, temperature 30 to 40°C, pH range 6 to 7, and time 2 to 6 hours.
2. The preparation method according to claim 1, characterized in that: The fabric in step (1) comprises a knitted fabric or a woven fabric formed from one or more of cotton, linen, silk, wool, viscose or tencel.
3. The preparation method according to claim 1, characterized in that: The concentration of the dextran sulfate solution in step (1) is 5-20 g / L, the concentration of the cross-linking agent is 1-5 g / L, the bath ratio is 1:8-20, the temperature of the reaction system is 50-60°C, the pH range is 8-9, and the time is 1-2 hours.
4. The preparation method according to claim 1, characterized in that: The initiator in step (2) is ammonium persulfate or horseradish peroxidase.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the 3,4-ethylenedioxythiophene to the initiator is 5-10:1-2.
6. The preparation method according to claim 1, characterized in that: The volume ratio of ethanol to water in the ethanol solution of step (2) is 1:6, and the concentration of 3,4-ethylenedioxythiophene is 5-10 g / L.
7. The polythiophene-based photothermal fabric prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the polythiophene-based photothermal fabric according to claim 7 in the preparation of functional textiles.